Long-Term Statin Use and Dementia Risk in Taiwan. (September 2014) - Chen, Ping-Yen; Liu, Shi-Kai; Chen, Chun-Lin; Wu, Chi-Shin
Background: The effect of statin use on dementia risk remains unclear. This study aims to examine the association between long-term statin use and dementia risk. Methods: A nest case–control study within a nationwide representative population-based cohort. Individuals aged 50 years and older participating in Taiwan's National Health Insurance program between 1998 and 2009 were enrolled. A total of 9257 patients with at least 3 outpatient or 1 inpatient claims records for dementia were identified. Comparison patients were selected at a 1:2 ratio from age- and sex-matched participants without dementia. The cumulative period and average daily dosages of statins, fibrates, and other lipid-lowering agents were measured. Results: The authors found a duration–response relationship, as dementia risk decreased by 9% per year of treatment of statins (adjusted odds ratio = 0.91; 95% confidence interval, 0.85-0.97). Use of high average dose statins for more than 1 year was associated with a lower risk of dementia than use of low average dose. However, there was no significant difference in dementia risks between lipophilic and hydrophilic statins. Fibrates or other lipid-lowering agents had no significant association with dementia risk. Conclusion: Our results suggest that long-term use of statin is associated with a reduced dementia risk.